2006
DOI: 10.1016/j.modgep.2005.06.003
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput screen for genes predominantly expressed in the ICM of mouse blastocysts by whole mount in situ hybridization

Abstract: Mammalian preimplantation embryos provide an excellent opportunity to study temporal and spatial gene expression in whole mount in situ hybridization (WISH). However, large-scale studies are made difficult by the size of the embryos (∼60 μm diameter) and their fragility. We have developed a chamber system that allows parallel processing of embryos without the aid of a microscope. We first selected 91 candidate genes that were transcription factors highly expressed in blastocysts, and more highly expressed in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 46 publications
3
62
0
Order By: Relevance
“…The expression of this gene was not detected in either ICM or TE in blastocysts by whole mount in situ hybridization (Yoshikawa et al, 2006). It has been shown that REST binds to the promoter region of Pou5f1 in ES cells (Boyer et al, 2005;Loh et al, 2006) and its expression is suppressed when Pou5f1 was repressed in mouse ES cells .…”
Section: Genes With Heterogeneous Expression Patterns (Mosaic-in-colomentioning
confidence: 97%
See 3 more Smart Citations
“…The expression of this gene was not detected in either ICM or TE in blastocysts by whole mount in situ hybridization (Yoshikawa et al, 2006). It has been shown that REST binds to the promoter region of Pou5f1 in ES cells (Boyer et al, 2005;Loh et al, 2006) and its expression is suppressed when Pou5f1 was repressed in mouse ES cells .…”
Section: Genes With Heterogeneous Expression Patterns (Mosaic-in-colomentioning
confidence: 97%
“…The expression of this gene was not detected in either ICM or TE in blastocysts by whole mount in situ hybridization (Yoshikawa et al, 2006). It has been shown that REST binds to the promoter region of Nanog was originally isolated as a gene whose overexpression maintains the undifferentiated state of ES cells in the absence of LIF and has been used as a marker for pluripotency (Chambers et al, 2003;Mitsui et al, 2003).…”
Section: Genes With Heterogeneous Expression Patterns (Mosaic-in-colomentioning
confidence: 99%
See 2 more Smart Citations
“…Although large-scale ISH/WISH methods have been applied to mouse intestine (Komiya et al, 1997), E9.5 embryos (Neidhardt et al, 2000;Gitton et al, 2002), and E9.5 and E10.5 embryos (Reymond et al, 2002), it has been difficult to apply this method to early embryos, because of their small size (ϳ80-m diameter in the case of preimplantation embryos) and fragility. This problem has been overcome recently by a chamber system that uses both transwell inserts for parallel processing and capillary action for gentle buffer exchanges (Yoshikawa et al, 2006).…”
Section: Small Size and Heterogeneity Of Embryonic Materialsmentioning
confidence: 99%